Integration of Digital Skills in Elementary School Learning: Facing Challenges in the 21st Century: Integrasi Keterampilan Digital dalam Pembelajaran di Sekolah Dasar : Menghadapi Tantangan di Era Abad 21 - Iis Hartati; Herma Susanah; Sofyan Iskandar (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2025)
In the 21st century, digital skills are increasingly needed in learning in elementary schools, considering that digital technology has become an inseparable part of daily life. This study uses a literature review approach to investigate various challenges faced by teachers in integrating technology into the teaching and learning process. Key findings show that many teachers still find it difficult to use digital devices, both hardware and software. In addition, low levels of digital literacy and lack of appropriate training exacerbate this situation. Another challenge that is also faced is limited access to technology, especially in areas with limited infrastructure. This article highlights the importance of improving relevant training programs and developing better infrastructure to support the utilization of technology in the classroom. By overcoming these obstacles, it is hoped that teachers can be more effective in using technology, which in turn will help students prepare for future challenges that are increasingly dependent on digital capabilities.